Moment loads acting on a blade of an ocean current turbine in shear flow. (15th January 2019) - Yahagi, Kazuomi; Takagi, Ken
Abstract: The Kuroshio flowing near Japan is one of the largest ocean currents and it is considered that this energy possibly be an important energy source for Japan. A full-scale generator with twin 40m turbine rotors is planned for at the rated flow speed of 1.5 m/s. Estimation of the blade loads are crucial for such big turbines. We focus on the effect of shear flow on an ocean current turbine and highlight the periodic fluctuation of moment loads at the blade root induced by the shear flow. Shear flow experiments and numerical computation with a commercial code were conducted for estimating the moment loads on a blade. The numerical computation was verified through the comparisons with the measured Cp and Ct in uniform flow. The numerical results of moment load in the shear flow are validated through the comparison with the experimental results. It is concluded that the moment loads are well estimated by the present CFD method. Using the same CFD method, some applications are shown. Hilights: We focus on the effect of shear flow. The peiodic fluctuation of moment loads at the blade root is hilited. Shear flow experiments and numerical computation has been done for estimating the fluctuation of moment loads on a blade. The numetical results showed that the larger gradient shear flow induces severe fluctuations of the loads.